Bilingual Teacher Talk Pada Pengajaran TEYL di Sepama Kamboja - Ratih Wijayava; Sri Marmoah; Farida Nurhasanah; Muhlis Fajar Wicaksana (Jurnal Ilmiah Dikdaya, 2023)
This study focuses on translation analysis of the use of bilingual teacher talk in teaching TEYL (Teaching English for Young Learners) in Sepama Cambodian classrooms. The method used is qualitative descriptive. The results showed that the students as teachers in the Sepama class used 8 translation techniques based on theories from Molina and Albirr. The results of the analysis were obtained based on the processing of 35 data obtained from online learning videos. The literal translation technique was applied to 9 data or 25.71%. Amplification technique as much as 2 data or 5.71%. Variation technique 1 data (2.85%), Typical matching technique 2 data or 5.71%. While the reduction technique has 9 data (25.71%). Transposition and particulate techniques each have 3 data or 8.57%. and finally Modulation technique as much as 4 data or 11.43%. The reduction technique is widely used because the structure of BSa is simpler than BSu. While literal techniques are also often used because teachers must immediately convey BSa and BSu immediately respectively.